Abdominal Massage as Nursing Implementation of Feeding Intolerance of Preterm Infants in Neonatal Intensive Care Unit: A Systematic Review - Darmareja, Rycco; Jansen, Susiana (Universitas Tribhuwana Tunggadewi, 2025)
The immaturity of the gastrointestinal tract of preterm infants can increase the prevalence of feeding intolerance that must be addressed by nurses. Massage is considered effective and is often used in neonatal intensive care. This study aims to identify the effectiveness of complementary therapy in the form of abdominal massage as a nursing implementation strategy for premature infants with feeding intolerance in the NICU. The study method refers to the PRISMA 2020 checklist with the following keywords: